Gestational Diabetes Mellitus (GDM) – Diagnosis, Treatment and Follow-Up. Guideline of the DDG and DGGG (S3 Level, AWMF Registry Number 057/008, February 2018) - Schäfer-Graf, Ute Margaretha; Gembruch, Ulrich; Kainer, Franz; Groten, Tanja; Hummel, Sandra; Hösli, Irene; Grieshop, Mellita; Kaltheuner, Matthias; Bührer, Christoph; Kautzky-Willer, Alexandra; Laubner, Katharina; Bancher-Todesca, Dagmar (Geburtshilfe und Frauenheilkunde, 2018)
A team of experts from the fields of gynaecology and obstetrics, diabetology, internal medicine, paediatrics and midwifery from Germany, Austria and Switzerland produced a new version of the existing S3 guideline on gestational diabetes. It replaces the recommendations of the German Association for Gynaecology and Obstetrics and the German Diabetes Association on the diagnosis and treatment of gestational diabetes from 2011 and is valid for the three German-speaking countries. The primary aim of the guideline is to improve and standardise the prevention, screening, diagnosis, treatment and follow-up of gestational diabetes through evidence-based recommendations for the outpatient and inpatient area. A large number of new studies and data published in the last few years required a comprehensive revision of the 2011 guideline. The new aspects include early screening of pregnant women with a high risk for diabetes or gestational diabetes, the validity of two-stage screening in the third trimester by means of the 50-g challenge test, as specified in the maternity guidelines, use of metformin instead of or in addition to insulin in gestational diabetes, and birth planning with GDM and/or macrosomia. The recommendations are based on the evidence from the literature, which was selected through a systematic external literature search. All recommendations had to pass through a consensus process. The present text corresponds to the practice guideline on gestational diabetes, which is an action-oriented short version of the evidence-based S3 guideline that can be viewed on the internet.Ein Expertenteam aus dem Bereich der Gynäkologie und Geburtshilfe, Diabetologie, Innere Medizin, Kinderheilkunde und Hebammenwissenschaften aus Deutschland, Österreich und Schweiz erstellte eine neue Version der bestehenden S3-Leitlinie zum Gestationsdiabetes. Sie ersetzt die Empfehlungen der Deutschen Gesellschaft für Gynäkologie und Geburtshilfe und der Deutschen Diabetesgesellschaft zur Diagnostik und Therapie des Gestationsdiabetes aus dem Jahr 2011 und ist für die 3 deutschsprachigen Länder gültig. Primäres Ziel der Leitlinie ist die Verbesserung und Vereinheitlichung von Prävention, Screening, Diagnostik, Therapie und Nachsorge bei Gestationsdiabetes durch evidenzbasierte Empfehlungen für den ambulanten und stationären Bereich. Eine Vielzahl von Veröffentlichungen neuer Studien und Daten der letzten Jahre erforderte eine umfassende Überarbeitung der Leitlinie von 2011. Die neuen Aspekte betreffen u. a. das Frühscreening bei Schwangeren mit hohem Risiko für Diabetes oder Gestationsdiabetes, die Validität des 2-stufigen Screenings im 3. Trimenon mittels 50-g-Suchtest, wie es in den Mutterschaftsrichtlinien vorgeschrieben ist, die Gabe von Metformin statt oder in Ergänzung zu Insulin bei Gestationsdiabetes und die Geburtsplanung bei GDM und/oder Makrosomie. Die Empfehlungen basieren auf der Evidenz, die sich aus der Literatur ergibt, deren Auswahl über eine systematische, externe Literatursuche erfolgte. Alle Empfehlungen mussten einen Konsensus-Prozess durchlaufen. Der vorliegende Text entspricht der Praxisleitlinie zum Gestationsdiabetes, die eine handlungsorientierte Kurzfassung der im Internet einsehbaren evidenzbasierten S3-Leitlinie ist.
Keywords: gestational diabetes; obstetrics; diabetes mellitus; pregnancy